Arabidopsis Class I Formin FH1 Relocates between Membrane Compartments during Root Cell Ontogeny and Associates with Plasmodesmata - Oulehlová, Denisa; Kollárová, Eva; Cifrová, Petra; Pejchar, Přemysl; Žárský, Viktor; Cvrčková, Fatima (Plant & cell physiology, 2019)
Formins are evolutionarily conserved eukaryotic proteins engaged in actin nucleation and other aspects of cytoskeletal organization. Angiosperms have two formin clades with multiple paralogs; typical plant Class I formins are integral membrane proteins that can anchor cytoskeletal structures to membranes. For the main Arabidopsis housekeeping Class I formin, FH1 (At3g25500), plasmalemma localization was documented in heterologous expression and overexpression studies. We previously showed that loss of FH1 function increases cotyledon epidermal pavement cell shape complexity via modification of actin and microtubule organization and dynamics. Here, we employ transgenic Arabidopsis expressing green fluorescent protein-tagged FH1 (FH1-GFP) from its native promoter to investigate in vivo behavior of this formin using advanced microscopy techniques. The fusion protein is functional, since its expression complements the fh1 loss-of-function mutant phenotype. Accidental overexpression of FH1-GFP results in a decrease in trichome branch number, while fh1 mutation has the opposite effect, indicating a general role of this formin in controlling cell shape complexity. Consistent with previous reports, FH1-GFP associates with membranes. However, the protein exhibits surprising actin- and secretory pathway-dependent dynamic localization and relocates between cellular endomembranes and the plasmalemma during cell division and differentiation in root tissues, with transient tonoplast localization at the transition/elongation zones border. FH1-GFP also accumulates in actin-rich regions of cortical cytoplasm and associates with plasmodesmata in both the cotyledon epidermis and root tissues. Together with previous reports from metazoan systems, this suggests that formins might have a shared (ancestral or convergent) role at cell-cell junctions.
Keywords: At3g25500; Endomembrane system; Arabidopsis; proteiny huseníčku; plazmodesmy; cytoskelet; Plasmodesmata; Arabidopsis thaliana; Arabidopsis Proteins; kořeny rostlin; Plant Roots; Vacuole; Cytoskeleton